(untitled) (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2022)
Introduction: Physical inactivity is a predisposing factor for developing non-communicable chronic diseases (NCDs). With the emergence of COVID-19, overweight and obesity have increased alarmingly. Objective: To determine physical activity levels and body mass index (BMI) during COVID-19 in secondary school teachers in the municipality of Sabanalarga, Atlántico, Colombia. Materials and Methods: This was a quantitative, descriptive, cross-sectional study. Six public secondary schools were selected by convenience, with a total population of 261 teachers, of which a sample of 109 participated in the survey (73 women and 36 men). Physical activity data were collected using the GPAQ questionnaire, and weight and height data were added to calculate BMI. The survey was distributed online via WhatsApp. Data were grouped and cleaned using Excel 2016, and statistical analysis was conducted with PSPP version 1.2. Results: A very high prevalence of physical inactivity was observed in women (54.8%), much lower in men (22.2%). Regarding overweight or obesity, 69.4% of men and 56.2% of women had this condition during COVID-19. No significant association was found between physical activity and BMI (p > 0.05). According to the results, teachers did not engage in physical activity during COVID-19 in any domain. Conclusion: Women were more physically inactive than men, while men had a higher prevalence of overweight or obesity than women during COVID-19. No statistical association was found between physical activity and BMI, although the findings highlight the importance of implementing physical activity programs in this population.